Patterned Inequalities and the Inequality Regime of a Swedish Housing Company - Boréus, Kristina; Mörkenstam, Ulf (Nordic Journal of Working Life Studies, 2015)
In this article, the authors analyze inequalities between different groups of employees at a housing company in a larger Swedish city. The concept of inequality regime is taken as a point of departure. The purposes of the article are three: first, to add to knowledge of how inequality is generated at an organizational level at specific workplaces; second, to contribute to the understanding of how different practices, processes, and meanings of inequality regimes may interact to create and reinforce inequalities between natives and immigrants; and, third, to contribute to the empirical usefulness of the concept of inequality regime by demonstrating how it can be operationalized and combined with other concepts in the analysis. The study shows how the practices, processes, and meanings at the given workplace generated and reproduced different kinds of inequalities: unequal wages, an ethnic division of labor, unequal influence and job security, and unequal opportunities to capitalize on useful skills (i.e., language competence). Important conclusions are that different kinds of inequalities may reinforce each other by creating vicious circles, and subtler forms of inequality may partly explain explicit wage inequalities.